# Cuatro cuatros ejercicio

Páginas: 3 (605 palabras) Publicado: 14 de diciembre de 2011
0 = 4 – 4 + 4 – 4
1 = 4/4 + 4 – 4
2 = (4/4) + (4/4)
3 = ((4*4) – 4)/4
4 = 4*(4 – 4) + 4
5 = sqrt(4)+sqrt(4)+4/4
6 = sqrt(4)*(4-4/4)
7 = 4 + 4 – 4/4
8 = 4*sqrt(4) + 4 – 4
9 =(4-4/4)^sqrt(4)
10 = 4*sqrt(4) + 4/sqrt(4)
11 = 44/(sqrt(4)*sqrt(4))
12 = (Sqrt(4) + Sqrt(4) + Sqrt(4))*Sqrt(4)
13 = 44/4 + sqrt(4)
14 = 4*4 – 4/sqrt(4)
15 = 44/4 + 4
16 =sqrt(4)*sqrt(4)*sqrt(4)*sqrt(4)
17 = 4^sqrt(4) + 4/4 = 4*4+4/4
18 = 4^(4/sqrt(4))+sqrt(4) = 44/sqrt(4)-4
19 = 4! – 4 – 4/4
20 = (4/4+4)*4
21 = 4! – 4/4 – sqrt(4)
22 = 44/(sqrt(4)*sqrt(4))
23 = 4! –sqrt(4)*sqrt(4)/4
24 = 4! + 4 – sqrt(4) – sqrt(4)
25 = 4! + sqrt(4)*sqrt(4)/4
26 = 4! + sqrt(4)*sqrt(4)/sqrt(4)
27 = 4! + 4/4 + sqrt(4)
28 = 4! + 4*4/4
29 = 4! + 4 + 4/4
30 = ((4+4/4)!)/4 31 = ((4! + 4) / 4) + 4!
32 = 4^sqrt(4)+4^sqrt(4)
33 = 44/(sqrt(.4…)*sqrt(4))
34 = ((4·4)·Sqrt(4)) + Sqrt(4)
35 = (4!) + (44/4)
36 = (4!*4!)/(4*4)
37 = ( 4! + Sqrt(4) ) / Sqrt(.4…)– Sqrt(4)
38 = 44 – (4 + Sqrt(4))
39 = ( 4! + 4 – Sqrt(4) ) / Sqrt(.4…)
40 = (4!) + (4!) – 4 – 4
41 = ( 4! + Sqrt(4) ) / Sqrt(.4…) + Sqrt(4)
42 = 44 – (4/Sqrt(4))
43 = 44 – (4/4)
44 =44 + 4 -4
45 = 44 + (4/4) = (4 + Sqrt(4))! / (4·4)
46 = ((4!)·4 – 4)/Sqrt(4)
47 = ((4!)·4 – Sqrt(4))/Sqrt(4)
48 = (4!)·Sqrt(4) + 4 – 4
49 = 4! * sqrt(4) + 4/4
50 = (4!)·Sqrt(4) + 4 –Sqrt(4)
51 = (4!/,4…) – Sqrt(4/,4…)
52 = (4!)·Sqrt(4) + Sqrt(4) + Sqrt(4)
53 = (4!/,4…) – 4/4
54 = (4!/,4…) + 4 – 4
55 = (4!/,4…) + 4/4
56 = 4! * sqrt(4) + 4 + 4
57 = (4!/,4…) +Sqrt(4/,4…)
58 = (4!/,4) – 4/Sqrt(4)
59 = (4!/,4…) + Sqrt(4)/,4
60 = (4!/,4…) + 4/Sqrt(,4…)
61 = (4!/,4) + 4/4
62 = (4!/,4…) + 4 + 4
63 = (4^4-4)/4
64 = 4! * sqrt(4) + 4 * 4
65 = (4!/,4) +Sqrt(4)/,4
66 = (4!/,4…) + 4!/Sqrt(4)
67 = ((4! + 4)/,4…) + 4
68 = (4!/,4) + 4 + 4
69 = (4!/,4) + 4/,4…
70 = (4!/,4…) + 4*4
71 = (4!+4.4)/.4
72 = (4!*4!)/(sqrt(4)*4)
73 = (4! + 4!...

Regístrate para leer el documento completo.